Faster Onset of Bronchodilation with Formoterol than with Salmeterol in Patients with Stable, Moderate-Severe Copd: Results of a Randomized, Double-Blind Clinical Study - John Kottakis; Giovanni Della Cioppa; Jacques Creemers; Louis Greefhorst; Violette Leclerc; Riccardo Pistelli; Tim Overend; Denise Till; Günter Rapatz; Vincent LeGros; Demosthenes Bouros; Nikolaos Siafakas (Canadian Respiratory Journal)
OBJECTIVES: To compare the onset and magnitude of bronchodilation after dry powder inhalations of formoterol fumarate (Foradil Aerolizer) versus salmeterol xinofoate (Serevent Diskus) with respect to normalized (*) forced expiratory volume in 1 s area under the curve 0 to 1 h after inhalation (FEV1 AUC*0-1 h).